PRARANCANGAN PABRIK ETILEN DARI NAFTA KAPASITAS 700.000 TON/TAHUN - , MOHAMMAD DZARNUJI AZIZ, Ahmad Tawfiequrrahman Y, S.T., MT. D. Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This ethylene plant was designed with a capacity of 700,000 tons per year. Ethylene is produced using naphtha as raw material by pyrolysis and planned to operate continuously for 330 days a year. The factory will be completely built in 2015. Ethylene plant consists of three main processes, namely thermal cracking, removing H2O and H2, separation and purification products. For the first process, the reaction is carried out in the pyrolysis heater, where cracking occurs at a very high temperature. Hydrocarbon gases go out of the reactor then gets quenched directly with water in the quench tower. Sudden cooling has a function to avoid further reaction, which is the polymerization reaction. Hydrocarbon gas goes in the separation and purification unit, consisting of five distillation towers, to be separated and purified to conform to the specifications desired for the product. To produce ethylene with 99.97% purity as much as 700,000 tons/year needs 2.689.162,60 tons/year of naphtha, 3.054.997,28 tons/year of steam and 100.016,67 tons/year of solvent. In addition to ethylene as the main product, this factory also produces propylene as much as 660.143,22 tons/year. Tools needed include 20,255,958.68 tons year of treated water, 758.633,30 m3/year of No. 2 fuel oil, 77.193,64 tons/year of methane refrigerant, 465.965,04 tons/year of ethylene refrigerant, 675,168,12 tons/year of ammonia refrigerant, 792,000 m3 of compressed air, and electricity generated at 48,016.59 kVA. The plant is planned to be established in the area of Cilegon, Banten on the land area of 200,000 m2 including the mess for employees and plans of regional expansion process. Employees needed are 494 people. Based on the criteria, the plant is considered high risk. The fixed capital for the plant is as much as $ 343.691.489,59 + Rp. 439.182.976.781,79 and the working capital as much as $ 898841685,7 + Rp. 107.012.513.178. While the total production cost is as much as $ 2.694.972.360 + Rp. 637.726.940.836,54 The profit before annual tax is Rp. 1.767.981.621.516,58 and the profit after tax is Rp. 883.990.810.758,29. The results of the economic analysis showed that the Return on Investment before tax is 38,74%